A molecular basis for nitric oxide sensing by soluble guanylate cyclase - Zhao, Yunde (The National Academy of Sciences, 1999)
Nitric oxide (NO) functions as a signaling agent by activation of the soluble isoform of guanylate cyclase (sGC), a heterodimeric hemoprotein. NO binds to the heme of sGC and triggers formation of cGMP from GTP. Here we report direct kinetic measurements of the multistep binding of NO to sGC and correlate these presteady state events with activation of enzyme catalysis. NO binds to sGC to form a six-coordinate, nonactivated, intermediate (k(on) > 1.4 × 10(8) M(−1)⋅s(−1) at 4°C). Subsequent release of the axial histidine heme ligand is shown to be the molecular step responsible for activation of the enzyme. The rate at which this step proceeds also depends on NO concentration (k = 2.4 × 10(5) M(−1)⋅s(−1) at 4°C), thus identifying a novel mode of regulation by NO. NO binding to the isolated heme domain of sGC was also rapid (k = 7.1 ± 2 × 10(8) M(−1)⋅s(−1) at 4°C); however, no intermediate was observed. The data show that sGC acts as an extremely fast, specific, and highly efficient trap for NO and that cleavage of the iron-histidine bond provides the driving force for activation of sGC. In addition, the kinetic data indicate that transport or stabilization of NO is not necessary for effective signal transmission.